Experimental investigation of stereocamera's error to optimize dust observation on HL-2A tokamak. (2nd October 2022) - Ma, Zhuang; Li, Wei; Li, Zhengyang; Huang, Zhihui; Shen, Jue; Huang, Dong; Huang, Yu; Liu, Zhuang; Gu, Liang; Lu, Shaoyu; He, Xiaoxue; Yan, Longwen; et al.
Abstract : An experimental investigation of the stereocamera's systematic error is carried out to optimize three-dimensional (3-D) dust observation on the HL-2A tokamak. It is found that a larger 3-D region occupied by all calibration points is able to reduce the 3-D reconstruction systematic error of the stereocamera. In addition, the 3-D reconstruction is the most accurate around the region where the calibration points are located. Based on these experimental results, the design of the stereocamera on the HL-2A tokamak is presented, and a set of practical procedures to optimize the 3-D reconstruction accuracy of the stereocamera are proposed.